Optimasi Kapsul Bawang Putih (Allium sativum Linn) sebagai Terapi Alternatif Pengobatan TBC - Yety Lindawati, Novena; Hartono (Jurnal Farmasi (Journal of Pharmacy), 2013)
Garlic (Allium Sativum Linn) proven inhibiting the Mycobacterium tuberculosis propagation. Alisin compound which implied in garlic (Allium Sativum Linn) functioning as wide spectrum antimikroba capable to pursue Tuberkulosis cause by bacterium. Garlic Capsule (Allium Sativum Linn) have to fulfill conditions as according to Decree Of The Minister For Public Health of Republic Indonesia No: 661/MENKES/SK/VII/1994 about traditional medicines. The results shows that garlic extract with 240 µg/ml medium (equivalent by 600 mg garlic extract per capsule) has better potency in pursuing growth of Mycobacterium tuberculosis (taken a from pure breeding colony from patient sputum culture which suffering Tuberkulosis BTA type + 2, positive culture 9, resisten to rifampisin) compared to 320 and 400 µg / ml media.Dry extract of garlic (Allium Sativum Linn) fulfilling conditions upon which fill traditional drug capsule, for example total plate number 1.5 (qualifying at the most 10); mould and khamir number 6x102 (qualifying at the most 104); negative result of patogen bacteries such as coliform bacteries, Eschericia Coli, Salmonella Sp, and Staphylococcus aureus; negatife result of of aflatoxin (qualify at the most 30 bpj); total water content equal to 1 - 2 % (qualifying at the most 10 %). Dry garlic extract (Allium Sativum Linn) capsule fulfilling conditions of pharmaceutical form of traditional capsule result disintegration time less than 13 minute (qualify at the most 15 minute) and fulfill uniformity of weight which qualify for the traditional capsule